Implementation of Certificateless Signcryption Based On Elliptic Curve Using Javascript - Abdul Wahid; Masahiro Mambo (International Journal of Computing and Informatics (IJCANDI), 2016)
Certificateless Cryptography (CLC) provides a new approach in addressing problems in encryption techniques. In CLC, any string can be used as a public key so that the data can be secured without using a certificate. In addition, the CLC concept makes it possible for the revocation of keys with a certain time limit. Another emerging concept is the signcryption which is a cryptographic system that combines the digital signature system and encryption system into one logical step thus requiring a smaller computational cost compared to the regular signature-then-encryption system. Elliptic Curve Cryptography (ECC) is a cryptography that uses elliptic curve which offers the same security but with smaller key sizes thus requiring less memory and computation. In this paper, we attempted to combine the three concepts to obtain all the advantages possessed by each concept without compromising system security. In the implementation we used client-based programming namely javascript which can reduce the workload of the server in order to achieve system security. We compared the computational cost of our scheme with some previous schemes and analyzed the security property of our scheme.